Formação de professores presencial-virtual: lógica concêntrica no desenvolvimento profissional e humano, trajetória pessoal, profissional e interdisciplinar do professor - Canales, Guillermo Eduardo Arancibia (2007)
The objective of the present research is to show that it is possible to carry out teacher training programs that combine face-to-face and virtual activities under the criteria of a new logic of teacher s education that synchronizes the space of teacher s personal development (human and life) and professional development. This program can be seen as a rupture from more traditional teacher training processes, which are based on quantity control measurement criteria, in order to allow new possibilities in teacher s practice. For the development of this research learning environment was constructed a for teachers enrolled in a master s program at a Chilean University, who took two consecutive subjects in curriculum in this graduate program. These subjects were carried out through a project of curricular intervention which incorporates the participants in a learning network (face-to-face and virtual). The methodology adopted tried to give meaning to teacher-students practice and performance, considering their double role. That is, students who gained new insights into their professional performance, and through a complex relational action which was generated from personal and professional integration. The creation of an appropriate methodology of qualitative analysis allowed the systematization of a significant volume of data of distinct typologies, registered in different activities, face-to-face and virtual ones, during two semesters of field work. The relational analysis of a series of emergent categories of a transversal nature associated with the teacherstudent training process was possible by using the computational tool CHIC (Hierarchical Classification, Implicative and Coercitive). The research characterized and developed the teacher training process as a recursive relational network. It is a formative trajectory of interdisciplinary orientation based on four dimensions which, in a progressive and interlinked way, operated around the formative dimension of the teacher s personal and human professional development. These dimensions correspond to a new logic based on the creation of the teacher s transversal categories (dimensions) which was named Concentric Logic in the Personal and Human Professional Development of Teacher Training. This logic characterizes teacher development as a complex relational phenomenon. Other results are related to the importance of emotional factors and the use of ICT (Information and Communication Technologies) as part of the teacher training process. Based upon these results a guide line is presented for teacher training programs